2019
DOI: 10.1111/jfpp.14096
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of turmeric drying using convection and microwave‐assisted drying technique: An optimization approach

Abstract: The aim of this study was to optimize the drying process of turmeric using convection drying followed by microwave drying to accelerate the drying time. Convection time (0-30 min) and microwave time (20-60 min) were the two investigation factors. The obtained dried turmeric was pulverized. Water, volatile oil, and curcuminoid contents were determined. Weight loss after drying was also investigated. Results showed that increasing the convection time and microwave time increased weight loss and decreased water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…A different trend was observed by Gounder et al, who reported the higher activity of cured (fresh rhizome boiled in water, dried in shade and polished) and dried rhizome oils over fresh ones [ 165 ], probably due to the lower percentage of ar-turmerone and β-turmerone. Anyway, the control of the drying conditions constitutes an important parameter in order to obtain the highest content of essential oil in the minimum time possible [ 166 , 167 ]. The sun and mechanical drying coexist as drying methods of C. longa rhizomes [ 156 ].…”
Section: Chemical Analysis Of the Essential Oil Obtained From mentioning
confidence: 99%
See 1 more Smart Citation
“…A different trend was observed by Gounder et al, who reported the higher activity of cured (fresh rhizome boiled in water, dried in shade and polished) and dried rhizome oils over fresh ones [ 165 ], probably due to the lower percentage of ar-turmerone and β-turmerone. Anyway, the control of the drying conditions constitutes an important parameter in order to obtain the highest content of essential oil in the minimum time possible [ 166 , 167 ]. The sun and mechanical drying coexist as drying methods of C. longa rhizomes [ 156 ].…”
Section: Chemical Analysis Of the Essential Oil Obtained From mentioning
confidence: 99%
“…The sun and mechanical drying coexist as drying methods of C. longa rhizomes [ 156 ]. In particular, Monton et al confirmed that one hour of microwave drying without conventional drying represented the optimum conditions to obtain the highest content of turmeric essential oil [ 167 ].…”
Section: Chemical Analysis Of the Essential Oil Obtained From mentioning
confidence: 99%
“…Therefore, an emerging drying technique with the purpose of making process of dehydration more sustainable is needed. Microwave based technique (Ali et al, 2020;Khan et al, 2016;Monton et al, 2019a) has exhibited its potential for drying i.e. reduced drying time and cost.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the data distribution was within 95% confident interval. It could be confirmed that the prediction by Design-Expert® software was stable [32][33][34][35][36]. Figure 7(a) shows that contour plots of the desirability of the optimal condition provided the simultaneous minimizing CI of the extraction yield and total content of the four phenolic compounds.…”
mentioning
confidence: 59%
“…They indicated that the data distribution was within 95% confident interval. It could be confirmed that the prediction by Design-Expert® software was stable [ 32 36 ].…”
Section: Resultsmentioning
confidence: 89%